STUDI CEKAMAN AIR TERHADAP PENAMPILAN BEBERAPA VARIETAS TANAMAN TOMAT (Lycopersicum esculentum, Mill.) - -, Mulyanto; Koentjoro, Yonny (MAPETA, 2000)
Almost every chemical processes in plant growth is always affected by water, in under field capacity condition of soil water contain often cause decreasing on plant growth and production, Because of its water could become very important factor and as limiting factor. Performance of plant is always controlled by interaction between charaters of genetic and environment condition. Every variety of plant'has different responses on environmental stress treatment, included water stress condition. This research is arranged in Completely Randomized Design with two factors and three times replication, Duncan test 5 % is used to compare the difference of every treatments. As the first factor is Water Stress with three levels are: C1 ( 75 % field capacity), C2 (100 % field capacity) and C3 (125 % field capacity) and the second factor is Variety of tomato with five levels are V1 (Sragen variety), V2(Lanjar Blitarvariety), V3 (LV 4066 variety), V4 (Jamaica Cherry variety) and V5 (Sinoloa variety). Results of this research shown that there were significant interaction between water stress treatment and variety on helqht of plant at 34, 44 and 54 days after plant and dry weight of plant. Sragen variety has tendency to adapted well on water stress treatment. Key words: Water Stress, Variety